Stabilization of a Subgrade Composed by Low Plasticity Clay with Rice Husk Ash - Ormeno, E. (2020)
The construction of road works in the world has always been a challenge for engineering, especially in areas where the conditions and types of soil are not adequate for the execution of this type of projects. The present investigation has as main objective to determine the influence that has the rice husk ash (RHA) to stabilize the subgrade layer of a pavement, composed of a low resistance clayey soil. RHA is a waste and pollutant material for the environment; therefore that its use can be considered as an economic and ecological alternative. Thus, several tests were carried out where it proved the value of CBR increased from 4.30% to 20.70%, by adding a 20% RHA dosage, achieving its optimum value to be considered a very good subgrade. In this way, it is possible to affirm that the addition of RHA improves the geotechnical properties of the soil.